Using specific length amplified fragment sequencing to construct the high-density genetic map for Vitis (Vitis vinifera L. × Vitis amurensis Rupr.) - Guo, Yinshan; Shi, Guangli; Liu, Zhendong; Zhao, Yuhui; Yang, Xiaoxu; Zhu, Junchi; Li, Kun; Guo, Xiuwu (Frontiers in Plant Science, 2015)
In this study, 149 F1 plants from the interspecific cross between ‘Red Globe’ (Vitis vinifera L.) and ‘Shuangyou’ (Vitis amurensis Rupr.) and the parent were used to construct a molecular genetic linkage map by using the specific length amplified fragment sequencing technique. DNA sequencing generated 41.282 Gb data consisting of 206,411,693 paired-end reads. The average sequencing depths were 68.35 for ‘Red Globe,’ 63.65 for ‘Shuangyou,’ and 8.01 for each progeny. In all, 115,629 high-quality specific length amplified fragments were detected, of which 42,279 were polymorphic. The genetic map was constructed using 7,199 of these polymorphic markers. These polymorphic markers were assigned to 19 linkage groups; the total length of the map was 1929.13 cM, with an average distance of 0.28 cM between each maker. To our knowledge, the genetic maps constructed in this study contain the largest number of molecular markers. These high-density genetic maps might form the basis for the fine quantitative trait loci mapping and molecular-assisted breeding of grape.